O trabalho e a formação do agente comunitário no programa saúde da família de Aracaju - Menezes, Rosana Marques de (2009)
The world of the work comes suffering modifications throughout the years with the process from globalization and the reorganization of the capital. This new world of the work modifies the productive process. New abilities are required of the worker emphasizing itself it polyvalence and the management for abilities. This research analyzes the occured transformations in the world of the work and its implications in the field of the Health making a relation between Work, Education and Health and has as objective generality to understand and to give to visibility to the work and the process of formation of the Communitarian Agent of Health in the Program Health of the Family of Aracaju. It analyzes the Politics of Permanent Education of the City department and Health department of Health of Aracaju and the contributions of the Course Technician for the formation and improvement of the practical professional of this important citizen of the Only System of Health. The research used the historical materialism. The qualitative boarding of ethnographic matrix revealed coherent for allowing the minute description of the objects that it investigates. It had as empirical field the sixth region of health of the city of Aracaju, counted on a universe of seventy and six communitarian agents of health and three agents of combat to the endemic diseases. It still counted on a sample of thirty communitarian agents of health and as chronological time understood between February of the 2006 finishing and the period year of the I Module of the Course Technician for Communitarian Agents of Health in December of 2007. The case study was prioritized and had been used the qualitative and quantitative boarding, a time that in the field of the Health, them if complements. It used for the production of the knowledge diverse pertaining documentary sources to the Center, City department, Health department of Health of Permanent Education of the Health, specialized magazines and sites. The empirical data had proven that the occured changes in the world of the work with the process of productive reorganization require a communitarian agent of health with a formation differentiated of the adopted one currently for the Health department and that the Permanent Education is a process necessary and valued by the diverse citizens however they point that the same one must be reviewed.